UMA PROPOSTA PARA INSERÇÃO DE REQUISITOS DE EFICIÊNCIA ENERGÉTICA NO PROCESSO DE PROJETO DE EDIFICAÇÕES PÚBLICAS - Cleff, Vinicius; Teixeira, Bruno; Hax, Douglas; Cunha, Eduardo; Schramm, Fábio (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This work proposes including requirements based on Brazilian Energy Efficiency Standards in the design process of governmental buildings, aiming to reduce unnecessary activities, such as rework, and consequently reduce their cost. A Focus Group was carried out, based on the stages from the Brazilian Architectural Design Standard (NBR 16636/17), with designers and experts in energy efficiency, in order to establish a consensus about when each requirement should be considered in the design process. This research can be useful to support designers by guiding them in the insertion of the energy efficiency requirements of buildings, adding value to the design process, by reducing activities that do not add value, especially reworking, besides make projects more energy efficient at a lower cost.